Aberrant Functional Network of Small-World in Sudden Sensorineural Hearing Loss With Tinnitus - Hua, Jin-Chao; Xu, Xiao-Min; Xu, Zhen-Gui; Xu, Jin-Jing; Hu, Jing-Hua; Xue, Yuan; Wu, Yuanqing (Frontiers in Neuroscience, 2022)
Few researches investigated the topological properties and relationships with cognitive deficits in sudden sensorineural hearing loss (SNHL) with tinnitus. To explore the topological characteristics of brain connectome following SNHL from the global level and nodal level, we recruited 36 bilateral SNHL patients with tinnitus and 37 well-matched healthy controls. Every subject underwent pure tone audiometry tests, neuropsychological assessments and MRI scanning. AAL atlas was employed to divide a brain into 90 cortical and subcortical regions of interest, then investigated the global and nodal properties of “small world” network in SNHL and control groups using a graph-theory analysis. The global characteristics include small worldness, cluster coefficient, characteristic path length, local efficiency and global efficiency. Node properties include degree centrality, betweenness centrality, nodal efficiency and nodal clustering coefficient. Interregional connectivity analysis was also computed among 90 nodes. We found that SNHL group had significantly higher hearing thresholds and cognitive impairments, as well as disrupted internal connections among 90 nodes. SNHL group displayed lower AUC of cluster coefficient, path length lambda, but increased global efficiency. The opercular and triangular part of inferior frontal gyrus, rectus gyrus, parahippocampal gyrus, precuneus and amygdala showed abnormal local features. Some of these connectome alterations were correlated with cognitive ability and duration of SNHL. This study may prove potential imaging biomarkers and treatment targets for future study.